Local area networks - CAMARATA, JOSEPH MICHAEL (1993)
A Local Area Network (LAN) is disclosed which enables a generalized data communication facility to be established over ordinary telephone wiring. The disclosed technique provides a completely general LAN architecture with any access protocol and is well suited to CSMA/CD (carrier sense, multiple access with collision detection). The invention consists of architectural and circuit techniques which enable the construction of a local area network(s) (LAN) over ordinary wiring within a building or between buildings within a short distance of each other (often called a campus). The LAN is implemented without disturbing the normal voice function of the telephone circuits and without the need to string addirional wiring. Implementing a LAN in accordance with this invention only requires three types of hardware functional elements (in the appropriate quantities for the application): (a) a Node Unit (NU), (b) Repeater Unit (RU), and (c) depending on the size of the network, possibly a Pulse Regenerator Unit (PRU).